Impact of relative humidity on the laying performance, egg quality, and physiological stress responses of laying hens exposed to high ambient temperature. (January 2022) - Kim, Da-Hye; Lee, Yoo-Kyung; Lee, Sung-Dae; Lee, Kyung-Woo
Abstract: The present study investigated the effects of relative humidity (RH) on the laying performance, egg quality, and stress indicators of laying hens raised at high ambient temperatures. A total of 180 Hy-Line Brown laying hens (68-wk-old) were randomly allotted to one of the following three RH conditions for 12 h a day (9:00 a.m.–9:00 p.m.) over four weeks: low RH (LRH; 25% RH), moderate RH (MRH; 50% RH), and high RH (HRH; 75% RH); ambient temperature was 30 °C under all treatments. None of the RH treatments affected hen-day egg production, egg weight, or egg mass (P > 0.05). However, feed intake was lower in the HRH group than in the LRH group (P < 0.05). Plasma corticosterone (CORT) concentration on day 21, yolk CORT concentration on day 3, and albumen CORT concentration on day 7 following RH exposure were higher in the HRH group than in the LRH group (P < 0.05). Moreover, plasma HDL-cholesterol concentration on day 14 was higher in the HRH group than in the LRH group (P < 0.05). On days 3 and 14, the Haugh unit decreased (P < 0.05) in the LRH group compared with that in the MRH and HRH groups. The HRH-exposed laying hens showed the lowest (P < 0.05) eggshell thickness on day 14. The absolute weights of eggshell, yolk, and albumen decreased in the HRH group compared with those in the MRH and LRH groups. Overall, high RH lowered feed intake and egg quality except for the Haugh unit, and induced stress response as manifested by elevated plasma, yolk, and albumen CORT concentrations. To our best knowledge, the present study is the first to demonstrate the role of RH in triggering temperature stress responses in laying hens. Highlights: The effects of relative humidity (RH) on the performance and physiology of laying hens were not well studied. RH did not affect hen-day egg production, egg weight, and egg mass. High RH lowered egg qualities but elevated corticosterone in eggs compared with low RH-exposed laying hens. RH plays an important role in environmental contributing factor triggering stress responses in laying hens.